Cultural values, popular attitudes and democracy promotion: how values mediate the effectiveness of donor support for term limits and LGBT+ rights in Uganda - Merran Hulse (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Democracy is frequently thought of as a “universal value”. Donors for the Organisation for Economic Cooperation and Development (OECD) accept this assumption and take measures in recipient countries that aim to promote or uphold values they consider central to democracy, including political competition and individual equality, among others. However, some scholars have questioned whether such values are actually universally applicable, and whether donors need to disavow themselves of the notion that “one size fits all” when it comes to promoting democracy in developing countries. Nevertheless, the role of cultural values in mediating the effectiveness of democracy promotion is relatively under-theorised in existing research. This discussion paper is part of the larger research project “What is democracy's value?”, which aims at understanding how societal values and attitudes influence the effectiveness of international democracy promotion in African countries. The project looks at how social values and political attitudes mediate democracy promotion in two specific realms: attempts by heads of state to circumvent presidential term limits, and reforms to legislation in the realm of family law and Lesbian, Gay, Bisexual, Transsexual (LGBT+) rights. This discussion paper focusses on two cases that took place in Uganda: Yoweri Museveni's successful 2005 campaign to remove presidential term limits from the Constitution, and the attempt to pass legislation outlawing homosexuality in 2014. In both cases, OECD donors intervened, to varying degrees, in an effort to uphold basic principles of democracy. Despite popular support for maintaining term limits, donor interventions were unsuccessful in the first case. They were, however, successful in thwarting the Anti-Homosexuality Act, even though it had a high level of popular support. The findings of the Ugandan case studies problematise the assumed link between cultural value dimensions – popularised by cross-cultural researchers such as Hofstede, Schwartz, and Inglehart and Welzel – and popular political attitudes. A tendency towards particular value dimensions does not necessarily seem to predispose Ugandans towards particular attitudes, nor does a match or mismatch between the value dimensions of donors and Ugandans result in a corresponding match or mismatch of political attitudes. Likewise, a widespread political attitude does not dictate the outcomes of reform processes, at least in the authoritarian context in which Ugandan politics takes place. More important is the magnitude of material incentives and/or sanctions offered by donors, and the transnational alliances between international and domestic actors. This is not to say that values do not matter. Cultural values are an integral part of the social and political contexts in which democracy promotion takes place and are an important factor in informing the behaviour of executive decision-makers. A greater understanding of cultural values, beliefs and attitudes is integral for both the study of democracy promotion and designing context-sensitive and effective interventions to support democracy in recipient countries.
Keywords: 330; Demokratie und Autokratie; Einstellungen; Werte und Normen